Zooplankton dilemma in the twilight (News & views) - Tedesco, Letizia (Springer Science and Business Media LLC, 2024)
Amidst the Arctic sea-ice decline and the consequent increasing under-ice light transmittance, Arctic zooplankton face challenging times. The collection of a unique dataset in the central Arctic Ocean unravels the patterns of their vertical migration, signalling potential disruptions to the Arctic ecosystem.